The Influence of Information Computer and Technology (ICT) Self-Efficacy and Entrepreneurial Learning on Technopreneurial Intention Among Engineering Students In Bandung City - Kriseka Putri, Mediany; Putra Budiman, Daffa Ardiya (Publikasi Indonesia, 2024)
The technology industry in Indonesia has experienced rapid growth, creating new opportunities for entrepreneurship in a field called technopreneurship. Small and Medium-sized Enterprises (SMEs), which contribute 61% to Indonesia's GDP, are undergoing a transformation by integrating online platforms and industrial processes. As of 2021, Indonesia ranked 74th out of 137 countries, with an entrepreneurship rate of 3.47%. This study aims to explore how ICT self-efficacy and entrepreneurial learning influence the intention to pursue technopreneurship among engineering students in Bandung. By understanding these factors, the research seeks to identify key elements in the formation of technopreneurs in Indonesia. The study employs a quantitative research method, using surveys to gather data. The survey is designed based on factors that influence the entrepreneurial intensity of engineering students. The research involves 382 samples from various universities in Bandung. Data will be analyzed using the Partial Least Square Structural Equation Model (PLS-SEM). The study tests three hypotheses, all of which show a positive and significant relationship between ICT self-efficacy, entrepreneurial learning, and technopreneurship intentions. The findings suggest that students with higher confidence in ICT and better entrepreneurial learning are more likely to have a strong intention to become technopreneurs. These results are expected to serve as a reference for universities in developing strategies to enhance technopreneurship interest among their students, contributing to the growth of the technopreneur ecosystem in Indonesia.